LANGUAGE AND IDENTITY IN CYBERSPACE. A MULTIDISCIPLINARY APPROACH - COTOC, Alexandra (2017)
The Internet and the digital world have created new opportunities for realtimeconversations among individuals who are geographically dispersed, butwho are sitting at their computer keyboards or are using other electronic devices.People post discourses and participate in “written” conversations in the newlinguistic genre, which combines characteristics of both written and oral language,but also features specific to the digital environment. They type their messages inchat exchanges, and these messages appear on the screens of their interlocutors,preceded by the sender’s cybername (name or nickname) (see Bechar-Israeli,2006); they register and create profiles on social network sites, blogs and gameplatforms.